1986
DOI: 10.18174/njas.v34i2.16810
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of veal calves in individual crates and in group pens.

Abstract: The differences in behaviour between calves in the two housing systems are discussed with regard to animal welfare. The behaviour of each calf was recorded by direct observation every 10 mins. over a 24 h period in weeks 8, 12, 16 and 20 after arrival for fattening at approx. 1 week. Lying posture, licking, head butting, mounting, intersucking and urine drinking were monitored. Group housing is seen as an important step towards improved calf welfare. This paper is based on part of a doctoral thesis published b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In general, group-housed calves are more difficult to load than individually kept calves (Trunkfield, 1990;Albright et al, 1991;Lensink et al, 2001). Albright et al (1991) suggested that Source: Longenbach and Heinrichs (1998).…”
Section: Vi) Handling Unweaned Calvesmentioning
confidence: 99%
“…In general, group-housed calves are more difficult to load than individually kept calves (Trunkfield, 1990;Albright et al, 1991;Lensink et al, 2001). Albright et al (1991) suggested that Source: Longenbach and Heinrichs (1998).…”
Section: Vi) Handling Unweaned Calvesmentioning
confidence: 99%
“…Calves need to rest and sleep in order to recover. They use several postures which include one in which they rest the head on the legs and another in which the legs are fully stretched out (De Wilt, 1985; Ketelaar‐de Lauwere and Smits, 1989; Ketelaar de Lauwere and Smits, 1991). Sleep disruption may occur if comfortable lying positions cannot be adopted or if there is disturbance to lying animals because they are trodden on or otherwise disturbed by other calves.…”
Section: Assessmentmentioning
confidence: 99%
“…Gregory et al reported that slips and falls were the main problems during loading [178], and Bravo et al found that slips and vocalizations were more common during unloading, whereas slips and turning around occurred more frequently during loading [179]. It has also been reported that group-housed calves are more difficult to load than individually kept calves [69,180,181]. While Albright et al found that grouphoused calves were more explorative when loaded onto a vehicle [180], and Trunkfield and Broom reported more balking and turning in group-housed calves than in individually housed calves [69].…”
Section: Fitness For Transportmentioning
confidence: 99%
“…It has also been reported that group-housed calves are more difficult to load than individually kept calves [69,180,181]. While Albright et al found that grouphoused calves were more explorative when loaded onto a vehicle [180], and Trunkfield and Broom reported more balking and turning in group-housed calves than in individually housed calves [69]. Lensink et al observed that group-housed calves stopped more often during loading, as indicated by the number of pushes performed by the handlers [181].…”
Section: Fitness For Transportmentioning
confidence: 99%